Reproductive Performance of the Ardennaise Chicken Breed under Traditional and Modern Breeding Management Systems - Lariviere, J- M.; Michaux, C.; Farnir, F.; Detilleux, J.; Verleyen, V.; Leroy, P. (International Journal of Poultry Science, 2009)
Enhancing the use of traditional chicken breeds is necessary to insure long-term conservation of global genetic diversity in poultry. A logical start in this process is to evaluate performance. The objective of this study was to estimate reproductive traits in the Ardennaise chicken breed under traditional and modern management systems. Reproductive performance indicated lighting programs [Natural (NAT) or Artificial (ART) day length] were highly significant for egg weight, hatchability (p<0.001), early and mid-term embryonic mortality (p<0.01). Feeding treatments [ad libitum (AL) or mild Feed-restriction (FR)] varied greatly with egg weight, hatchability, fertility (p<0.001) and late embryonic mortality (p<0.05). Most precocious age at first egg (23 weeks), longest duration of laying period (>27 weeks), utmost maximum production peak (56.67%), largest egg number (70.13 eggs/hen) and number of chicks hatched (24.10 chicks/hen) were performed under ART-AL. Heaviest egg weight (53.21g), highest fertility (70.20%), greatest hatchability (55.58%), highest liveability during rearing (95.74%) and lay (100%), lowest early (3.51%) and mid-term embryonic mortality (1.17%) were achieved under NAT-AL. To summarize, most of traits studied in the Ardennaise chicken were moderate when compared to those expected by broiler breeders.